2016
DOI: 10.1108/oir-08-2015-0274
|View full text |Cite
|
Sign up to set email alerts
|

Session identification techniques used in web usage mining

Abstract: Purpose The purpose of this paper is to critically analyze the state-of-the-art session identification techniques used in web usage mining (WUM) process in terms of their limitations, features, and methodologies. Design/methodology/approach In this research, systematic literature review has been conducted using review protocol approach. The methodology consisted of a comprehensive search for relevant literature over the period of 2005-2015, using four online database repositories (i.e. IEEE, Springer, ACM Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Prior research has proposed various strategies to determine appropriate session boundaries, such as time-oriented heuristics, imposing a threshold on the total session duration (usually 30 minutes) or a maximum duration limit on a specific page (generally 10 minutes) (Cooley et al, 1999); navigation-based heuristics, making use of browser navigation, i.e., examining the structure of the website to identify user sessions: when two sequential logs refer to pages which are not directly connected, a new user session begins (Nadjarbashi-Noghani & Ghorbani, 2004); task-based heuristics, finding groups of semantically related search queries tackling the same task (Boldi et al, 2008;Jones & Klinkner, 2008); or employing meaningful transactions identified using a reference length approach (Fatima et al, 2016).…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has proposed various strategies to determine appropriate session boundaries, such as time-oriented heuristics, imposing a threshold on the total session duration (usually 30 minutes) or a maximum duration limit on a specific page (generally 10 minutes) (Cooley et al, 1999); navigation-based heuristics, making use of browser navigation, i.e., examining the structure of the website to identify user sessions: when two sequential logs refer to pages which are not directly connected, a new user session begins (Nadjarbashi-Noghani & Ghorbani, 2004); task-based heuristics, finding groups of semantically related search queries tackling the same task (Boldi et al, 2008;Jones & Klinkner, 2008); or employing meaningful transactions identified using a reference length approach (Fatima et al, 2016).…”
Section: Background and Related Workmentioning
confidence: 99%
“…For a web search, usually, a session is addressed as specific brief sequences of queries submitted to the web search engine by a user to address a single information need (Jansen et al, 2007), and search sessions are temporal sequences of queries issued by users (Lucchese et al, 2013). However, there have been many attempts to segment and define sessions that do not directly address the concept of user information demands but rely on the concept of similar context, topic, or temporal characteristics (Jones & Klinkner, 2008;Fatima et al, 2016).…”
Section: Background and Related Workmentioning
confidence: 99%
“…In addition, he will share experiences, skills and problems afflicting him in the work environment and receive guidance from other users. User identification is necessary to set what will be accessed and for how long with the help of algorithms in a digital environment (Fatima et al , 2016).…”
Section: Theoretical B2b Knowledge Management Framework Focused On Va...mentioning
confidence: 99%
“…A web usage mining method is proposed [1], this method can be applied to solve the problem of developing more accurate and efficient recommendation systems, the traditional data protection mechanism focuses on the access control and the secure transmission, which provide only security against malicious the third parties, but not the service provider, so this method can mine efficiently and intelligently data, in order to guide and track the users' usage behavior, and does main contribution in the application direction of the modern Ebusiness. A web usage mining method is proposed [11], in this method, the state-of-the-art session identification technology is used in terms of limitation, feature, and methodology, which provide a structured overview of the research development, in this technical context, the comparative experiments critically review existing session identification technology, the whole research result does main contribution in highlighting the limitation and related challenge, identifying the area where further improvement is required, in order to complement the performance of existing technology. A web usage mining method is proposed [21], in this method, an algorithm is also designed for the data cleaning and filtering using the web log dataset, this algorithm mainly complete the process of preprocessing and clustering the usage behavior, which consists of the use cases for the data cleaning and filtering, the user and session identification, in this technical context, the experiments are carried out to obtain the aggregate clustering results, through this process, two datasets of web usage log are collected and processed, so the whole research result does main contribution in the area of web usage behavior analysis.…”
Section: Related Workmentioning
confidence: 99%